La precarización laboral en el sector laboral del cantón Echeandía en el año 2021. - Riera Carvajal, Wendy Leticia (2023)
The purpose of this research work on labor precariousness in the labor sector is to explain the way in which workers' rights are violated, where the employer, for various reasons, takes advantage of them, infringing their rights and causing this to lead to insecurity, uncertainty and lack of guarantees in working conditions. It should be noted that labor precariousness has a special incidence in the Ecuadorian legal system. In order to understand the subject in the background, historical facts are collected and it is possible to understand how the violation of workers' rights arises through precariousness, despite the fact that the 2008 Constitution guarantees the right to a decent and fair salary, recognizing all the legal benefits to which workers are entitled. On the other hand, this research work is fully justified because it deals with a real and current issue where the intention is to demonstrate the violation of the constitutional right to work and how labor precariousness has been reducing the possibilities of a decent job for people. In the same way, the problem details the subjection to the sole will of the employer or assignor, subjecting the renewal to his will at any time, even more aggravated this problem when in art. 20, 1 and 2 of the Organic Law of Humanitarian Support of 2020, which approves the emerging reduction of the working day in which it is provided that "the remuneration of the worker will correspond, in proportion to the hours actually worked and will not be less than fifty-five percent of that fixed prior to the reduction" (Organic Law of Humanitarian Support, 2020, p. 9). 9) We can warn that being a duty of the State to generate conditions of integral protection to the worker has not been done, these issues have been addressed only from the business perspective favoring the employer, a situation that is becoming increasingly critical in our country and even more so in small cities such as in the Canton Echeandía where labor precariousness is increasingly accentuated. In order to comply with the purposes established in this research, measurable and achievable objectives have been set to understand the problem from a critical analysis that leads to a possible solution based on the identification of variables and the establishment of the assumption that labor precariousness should be treated in Ecuadorian 14 legislation in such a way that it favors the just rights of the worker. In order to provide a theoretical and legal basis for the research, the theoretical framework describes relevant topics that will help to understand the problem from another perspective and finally, conclusions are drawn that will allow us to reflect on the real situation of the worker in the Echeandía Canton, thus allowing us to make favorable recommendations in favor of this very important sector.